2017
DOI: 10.3329/bjmm.v10i1.31449
|View full text |Cite
|
Sign up to set email alerts
|

Study of Bacterial pathogens in Urinary Tract Infection and their antibiotic resistance profile in a tertiary care hospital of Bangladesh

Abstract: Analyzing antibiotic susceptibility pattern of uropathogens help to overcome the therapeutic difficulties created by the rising antimicrobial resistant bacteria and guides in choosing appropriate antibiotics. Hence, we aimed at evaluating the pathogens causing UTI and study their antibiogram. Midstream urine samples were collected, cultured and appropriate biochemical tests were performed for proper identification of urinary pathogens in BSMMU from January 2013 to December 2013. The most common isolated Gram n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
7
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
(20 reference statements)
5
7
2
Order By: Relevance
“…Almost similar high resistance pattern was reported in Iran and Nigeria. 35,36 But in contrary to our findings, other studies have reported that greater percentage of UTI isolates were sensitive to this antibiotic. 21,23,33 Nitrofurantoin was considered drug of choice for UTI, as it was found to be reasonably high efficacious agent among all antimicrobials used against uropathogens.…”
Section: Discussioncontrasting
confidence: 99%
“…Almost similar high resistance pattern was reported in Iran and Nigeria. 35,36 But in contrary to our findings, other studies have reported that greater percentage of UTI isolates were sensitive to this antibiotic. 21,23,33 Nitrofurantoin was considered drug of choice for UTI, as it was found to be reasonably high efficacious agent among all antimicrobials used against uropathogens.…”
Section: Discussioncontrasting
confidence: 99%
“…Even Ciprofloxacin resistance rate (79.66%) to E coli is higher in one study in Saudi Arabia. [28][29][30] A multicenter study of 13 countries in the Asia-Pacific region from 2010-2013 reported lower susceptibility to Ciprofloxacin support our study. [ Second and third-generation Cephalosporins are commonly used empirical agents for both uncomplicated and complicated UTIs patients in any context.…”
Section: Discussionsupporting
confidence: 78%
“…This study was conducted in the paediatric population but still showed similar findings to our study which was conducted in the adult population. Another study carried out by Setu et al 18 in Dhaka, Bangladesh in 2015 showed the highest isolation rates of Escherichia coli and Klebsiella pneumonia in gramnegative species and S. aureus in gram-positive species. The highest levels of antibiotic resistance were found to Amoxicillin (77%), Nalidixic acid (63%), and Ceftriaxone (56%).…”
Section: Discussionmentioning
confidence: 94%